Reconstruction of Islamic Thought: An Epistemological Approach to Advancing Islamic Education - hosaini hosaini; Syamsun Ni’am; Akhmad Rizqon Khamami; Mahtukhin Mahtukhin; Musawer Hakimi (At-Tarbiyat, 2024)
This research is motivated by the emergence of the assumption that science is said to be scientific if it can be proven empirically and can be accepted by reason. Although the epistemological instruments of Islamic studies are different from Western epistemological instruments, Islam legitimises this opinion by arguing that the most valid level of validity of science only comes from revelation without denying the truth of science obtained through empirical and rational sources. This research was studied using the SLR (Systematic Literature Review) approach. Data were collected from various journals and books relevant to the themes raised in this study. The results of data analysis found that science is said to be scientific if it can be proven empirically and rationally, this opinion is expressed by Western scientists. Whereas in the Islamic view, such as the opinion of Muslim philosophers such as Al-Kindi, Al-Farabi, Ibn Rushd, and Ibn Sina, science will reach the level of scientific validity if it comes from revelation, belief, and sometimes obtained through inspiration. The findings of this study confirm that the Islamic epistemological approach can contribute significantly in advancing Islamic education, by combining empirical, rational, and revelation sources as the basis for developing science.